Low-income transfer engineering undergraduates’ benefits and costs of online learning during COVID-19 - Lee, Hye Rin; Yang, Kaidan; Rutherford, Teomara; Ramirez, Kevin F.; Eccles, Jacquelynne S. (Frontiers in Education, 2023)
Online courses were a common and growing format for higher education even before the COVID-19 pandemic, but selection effects made it difficult to understand and generalize about low-income transfer engineering students’ perceptions regarding online course experiences. However, the forced transition from face-to-face courses to online courses as a result of COVID-19 provided researchers and educators the opportunity to examine low-income transfer engineering students’ online learning experiences without selection effects. Using a naturalistic method, the present study examined low-income transfer engineering students’ (N = 7) communicated perceived benefits and costs of online learning during the pandemic. Analysis using inductive coding found three overarching themes of benefits and costs: benefits and costs related to the learning environment, benefits and costs related to the format of instruction, and benefits and costs related to external factors. Students named studying at their own pace as the most frequently occurring benefit of online learning. On the other hand, difficulty self-regulating was the most frequently named cost of online learning. Implications for theory, practice, and future work are discussed.